(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Cross-sectional descriptive study was conducted on 270 patients with vaginitis who visited Tan Tao University of Medicine Hospital, Long An, to determine the prevalence of Candida spp infection, composition species and related factors. Research methods: Data was collected through direct interview using a pre – designed questionnaires combined with gynecological examination. Candida spp infection was determined by direct microscopy, species identification culture on Sabouraud and Chromagar Candida media. Results: The rate of Candida spp infection was 15.9%. C. albicans accounted for 79.1%, followed by C. glabrata 16.3%, C. krusei and C. tropicalis had same rate of 2.3%. Women living in urban areas had a 2.57 times higher rate of Candida spp vaginitis compare to those with rural areas (CI95%: 1.14 - 5.88, p = 0.02); Women using oral contraceptives had a 4.49 times higher rate of Candida spp vaginitis compare to those not using them (95% CI: 2.22 – 9.08, p < 0.001); Women using unknown long-term drugs had 3.51 times higher rate of Candida spp vaginitis compare to those not using drugs (95% CI: 1.17 – 10.55, p = 0.025).